Answer:
#1. How to solve your question
Your question is
3(2+4)=2(2−2)
3(2x+4)=2(2x-2)3(2x+4)=2(2x−2)
Solve
1
Distribute
3(2+4)=2(2−2)
{\color{#c92786}{3(2x+4)}}=2(2x-2)3(2x+4)=2(2x−2)
6+12=2(2−2)
{\color{#c92786}{6x+12}}=2(2x-2)6x+12=2(2x−2)
2
Distribute
again
6+12=2(2−2)
6x+12={\color{#c92786}{2(2x-2)}}6x+12=2(2x−2)
6+12=4−4
6x+12={\color{#c92786}{4x-4}}6x+12=4x−4
3
Subtract
12
1212
from both sides of the equation
6+12=4−4
6x+12=4x-46x+12=4x−4
6+12−12=4−4−12
6x+12{\color{#c92786}{-12}}=4x-4{\color{#c92786}{-12}}6x+12−12=4x−4−12
4
Simplify
Subtract the numbers
Subtract the numbers
again
6=4−16
6x=4x-166x=4x−16
5
Subtract
4
4x4x
from both sides of the equation
6=4−16
6x=4x-166x=4x−16
6−4=4−16−4
6x{\color{#c92786}{-4x}}=4x-16{\color{#c92786}{-4x}}6x−4x=4x−16−4x
6
Simplify
Combine like terms
Combine like terms
again
2=−16
2x=-162x=−16
7
Divide both sides of the equation by the same term
2=−16
2x=-162x=−16
22=−162
\frac{2x}{{\color{#c92786}{2}}}=\frac{-16}{{\color{#c92786}{2}}}22x=2−16
8
Simplify
Cancel terms that are in both the numerator and denominator